ANALISIS DAYA GABUNG HASIL PERSILANGAN DIALEL BEBERAPA VARIETAS PADI (Oriza sativa L.) MENGGUNAKAN METODE GRIFFING - Sofi Rianti (CROP AGRO, Scientific Journal of Agronomy, 2020)
ABSTRACT This research aims to determine the general combining ability and special combining ability of the cross-diallel results of several varieties of rice plants using the griffing method. The study was conducted in technical irrigated rice fields, the experimental station of the Faculty of Agriculture, University of Mataram in the Village of Nyur Lembang, Narmada District, West Lombok Regency from February to July 2019. The experimental design used in this study was a Randomized Block Design (RBD) using the dialel griffing II method consisting of 4 parental and F1 crossing results. The results showed that combinimg ability the seven characters have a positive.Keywords: rice, dialel crossing, combining power, griffing method.